Membangun Kesadaran Berbahasa : Memahami Sejarah Bahasa Indonesia Dan Kemunculan Bahasa Gaul Di Era Globalisasi - Sri Handayani Rahmani; Aisha Eliana Putri; Fifi Nur Alifiah; Ghina S yahira Idham (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Indonesian as a national language has an important role in preserving identity and cultural diversity in Indonesia. This research aims to examine the origin and development of Indonesian through library research and historical methods whose stages consist of Heuristics or source collection, source criticism, Interpretation, Historiography. By utilizing library sources, this research found that Indonesian originated from the Malay language, Riau. In addition, Indonesian underwent three phases of development, namely as a language of unity, official state language, and international language. The development process of Bahasa Indonesia started from its birth on October 28, 1928 until the ratification of Law Number 24 of 2009. These phases reflect the evolution of Indonesian as the main means of communication in Indonesia, from its role as a language of unity in the fight against colonialism to becoming the official state language and international language in the era of globalization and modernization. The importance of the role of mass media in fostering and developing Indonesian is also highlighted in this study. Mass media has a role in strengthening the use of Indonesian as an effective communication tool in conveying information and enriching vocabulary and language structure. The conclusion of this study emphasizes the importance of preserving and developing Indonesian as a national identity that not only unites the Indonesian nation, but also becomes a communication medium.